Spectral Features of the Energy-containing Range and the Inertial Range in Fast Solar Wind Turbulence - Wu, Honghong; Huang, Shiyong; Yang, Liping; He, Jiansen; Yuan, Zhigang (The Astrophysical journal, 2025)
Power spectra of the fluctuations provide a baseline to interpret the solar wind turbulence in the magnetohydrodynamic scale. The magnetic spectra show a typical index of −1 in the low-frequency range, which is regarded as the energy-containing region. Recent studies show that it can be much shallower than 1/ f in the near-Sun solar wind, indicating that there is a dynamic origin for the 1/ f range formation. However, the nature of the energy-containing range remains unanswered. Here we investigate 97 fast solar wind intervals, each with time durations ≥2 days at 1 au observed by the Wind spacecraft from 2005 to 2018. We perform the spectral analyses and find that the spectral index in the energy-containing range is −0.78 ± 0.22 for the magnetic field and −1.49 ± 0.30 for the velocity. To compare, the spectral index in the inertial range is −1.60 ± 0.04 for the magnetic field and −1.51 ± 0.04 for the velocity. In both ranges, the indices for the magnetic field and the velocity are correlated. The cross helicity σ c grows to the saturation level before the break between the two ranges. The saturation level is correlated with the magnetic spectral index in the inertial range and the velocity spectral index in the energy-containing range. Our findings provide new clues for the origin of the energy source and help understand the evolution from the energy-containing range to the inertial range.